Experimental insights of using waste marble fines to modify the geotechnical properties of a lateritic soil - I. Akinwumi, Isaac; A. Booth, Colin (Journal of Environmental Engineering and Landscape Management, 2015)
Marble spoil waste is an environmental nuisance. The effects of adding waste marble fines (WMF) on the plasticity, strength and permeability of a lateritic clay have been investigated for its potential use as a soil modifier or stabilizer of road pavement layer materials or earth-building materials. The chemical compositions of the WMF and soil were determined using X-ray fluorescence and atomic absorption spectrometry, respectively. The specific gravity, Atterberg limits, compaction, strength and permeability characteristics of the soil were determined for varying proportions of the soil-WMF blends. The properties of the natural soil – classified as clay of low plasticity (CL) andA-7-6(7), according to unified soil classification and AASHTO classification systems, respectively – were improved after the addition of 10% WMF such that it behaves like a silt of low plasticity. Therefore, WMF is recommended as a low-cost soil modifier or stabilizer for lateritic soil and well-suited for road construction applications.